THE EFFECT OF GOOGLE SITES ON ELEMENTARY STUDENTS’ CONCEPTUAL UNDERSTANDING IN MATHEMATICS - Riyanto, Hendra Wahyu; Degeng, I Nyoman Sudana; Sitompul, Nurmida Catherine (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
The advancement of digital technology has transformed primary education, particularly in geometry learning, which relies heavily on visual-spatial skills. This study aims to examine the influence of Google Sites compared to e-books, as well as the role of visual-spatial intelligence, on fourth-grade students’ understanding of area and volume concepts. A quasi-experimental method with a 2x2 factorial design was employed, involving 62 students from SDN Losari, Jombang. The research instruments were validated and found to be reliable. Two-way ANOVA results indicated that both learning media and visual-spatial intelligence significantly affected students’ conceptual understanding (p < 0.05), with a significant interaction between the two variables. Students with high visual-spatial intelligence who used Google Sites achieved the highest learning outcomes. These findings highlight the effectiveness of interactive digital media and the importance of aligning instruction with students’ cognitive characteristics. It is recommended that teachers integrate web-based tools like Google Sites, especially for topics requiring spatial visualization, to foster more adaptive and meaningful learning experiences.